Suppression of mycotoxins production and efficient chelation of heavy metals using natural melanin originated from Aspergillus flavus and Aspergillus carbonarius - Nashwa El-Gazzar; Esraa Abdo; Gamal Rabie; Manal Tawfeek El-Sayed (BMC Biotechnology)
Abstract Background This study employed melanin synthesized by Aspergillus flavus and Aspergillus carbonarius to inhibit the production of mycotoxins and bioremediation of heavy metals (HMs). Methods First, twenty fungal isolates were obtained from soil samples, and were evaluated to produce melanin. The melanin of the most potent producers has undergone several confirmatory experiments, including, Dihydroxyphenylalanine (DOPA)-inhibitor-kojic acid pathway detection, High-performance liquid chromatography (HPLC), Fourier-transform infrared (FTIR) and Nuclear magnetic resonance (NMR). Additionally, the melanin production culture conditions were optimized. The antioxidant activity of melanin was detected with 1,1-Diphenyl-2-picrylhydrazyl (DPPH). HPLC was used to measure the mycotoxins produced in culture media supplemented with melanin. Molecular docking study investigated molecular interactions between melanin and mycotoxins through in silico approaches. FTIR and Energy-dispersive X-ray spectroscopy (EDX) were utilized to determine the percentage of melanin-chelated HMs, and an atomic absorption spectrophotometer (AAS) was used to detect HMs removal efficiency. Results The melanin-enriched medium (0.3% and 0.4%) exhibited complete inhibition of aflatoxin B1 (AF-B1) by A. flavus and ochratoxin A (OTA) by A. carbonarius, respectively. Furthermore, melanin showed effective HM removal efficiency, increasing with melanin concentration. The removal efficiency of Cd+2 and Cr+6 by 1 mg/mL melanin was 49% and 63%, respectively. When the concentration of melanin was increased to 15 mg/mL, the removal efficiency of Cd+2 and Cr+2 increased to 60% and 77%, respectively. Conclusion The study exhibited a natural approach for melanin production, using melanin as a heavy metal-chelating agent and capability to inhibit the production of aflatoxin B1 and ochratoxin A. Further, the study provides significant evidence regarding the bioremediation pipeline, for melanin production through biotechnological processes by filamentous fungi.